Detection of environmental DNA of finless porpoise (Neophocaena asiaeorientalis) in Osaka Bay, Japan - Nagisa Hashimoto; Takashi Iwata; Natsumi Kihara; Kiyomi Nakamura; Masayuki K. Sakata; Toshifumi Minamoto (Conservation Genetics Resources, 2024)
Finless porpoises ( Neophocaena asiaeorientalis ) currently face population decline caused by significant human activities and are categorized as endangered on the International Union for Conservation of Nature (IUCN) Red List; however, information on their habitats is currently insufficient. Although conducting visual surveys to determine the distribution of cetaceans is common, visual observation of finless porpoises is challenging owing to their specific morphological and ecological characteristics. In this study, we developed an environmental DNA (eDNA) assay for species-specific detection of finless porpoises. To test the utility of the assay, we conducted a visual survey in parallel with an eDNA survey by collecting water samples from 50 sites throughout Osaka Bay. We visually found a finless porpoise at one location and detected eDNA at nine sites, including sites near the visual observation site and those with rare sightings of finless porpoises. Therefore, in this study, we suggest that the use of eDNA analysis for distribution surveys of finless porpoises will enable more efficient surveys. The proposed eDNA technique can not only be applied to the distribution surveys finless porpoises but also to those of other cetacean species.